Costs of dental rehabilitation: state policies to reduce inequalities - Marín, Gustavo Horacio (2015)
In Latin American countries, oral health is seen by health’s authorities as a luxury good because of the high costs for health system. In Argentina 33 % of population had lost teeth when they reach young adults age. To determinate the cost either in public or private sector of a dental health care program for population with severe dental problems. We conducted a prospective study where dental health status, type of prostheses, cost of prostheses, quality of life and patient’s socio-economic conditions were considered variables. Patient’s selection was randomized performed among volunteers with dental pieces missed. Two groups were considered: patients in whom prostheses were provided by a public program (group A); and another group where prostheses were accessed in the private sector. The average cost to provide prostheses and oral rehabilitation per patient was € 1785.38 in the private sector while for the state program was € 268.51, which meant over 85% of saving. High satisfaction of users and an increased self-confidence of patients were achieved. This paper evidences a low-cost State program that reduced 85% the regular prices for dental prostheses. This experience can provide the groundwork for massively increase access to oral health care.